Local Prophylactic Teicoplanin Effect on Spinal Fusion Surgery: A Comparative Retrospective Study - Elmadağ, Nuh Mehmet; Kara, Deniz; Pulatkan, Anil; Uçan, Vahdet; Cesme, Dilek Hacer; Aliyev, Orkhan; Doğu, Hüseyin; Demirel, Nail; Abdallah, Anas (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Surgical site infection (SSI) is one of the most severe complications of spinal fusion surgery that lead to increased morbidity and mortality rates. Prophylactic antibiotic usage is one of the methods that reduce the possibility of SSI in this procedure. The aim of this study was to determine the effect of local subfascial teicoplanin usage on radiologic and functional outcomes and compare it to the effect of vancomycin on surgical outcomes in patients who underwent decompression with posterior instrumentation (DPI) for lumbar spinal stenosis (LSS).Methods Medical charts of patients with LSS who received DPI and met the study criteria were divided into three groups: the teicoplanin group included patients who underwent DPI with local teicoplanin before closure, the vancomycin group included patients who underwent DPI with local vancomycin, and the control group included patients who underwent DPI without any local prophylactic antibiotics.Results A total of 101 patients were included in the study. No significant differences were found among groups regarding demographics, follow-up, and clinical and functional outcomes. No significant differences were observed among groups regarding postoperative improvements in SF-36-MCS, SF-36-PCS, Oswestry Disability Index, and Visual Analog Scale (VAS; p > 0.05). In the teicoplanin and vancomycin groups, the SSI rate was lower than that in the control group (2/35, 1/34, and 5/32, respectively, p = 0.136) without statistical significance; however, the postoperative fusion volume was significantly higher in the teicoplanin group when compared to the other groups (3.35 ± 1.08, 2.68 ± 1.17, and 2.65 ± 1.28 cm3, respectively, p = 0.007).Conclusions Although its cost is relatively higher, teicoplanin was a good alternative to vancomycin in preventing SSIs with a higher fusion rate, but no superiority was observed regarding other outcomes.
Keywords: surgical site infections; spinal fusion surgery; prophylactic antibiotics; teicoplanin; vancomycin; fusion mass